Multifactorial vascular risk factor intervention to prevent cognitive impairment after stroke and TIA: a 12‐month randomized controlled trial. Issue 7 (4th December 2012) - Ihle‐Hansen, Hege; Thommessen, Bente; Fagerland, Morten W.; Øksengård, Anne R.; Wyller, Torgeir B.; Engedal, Knut; Fure, Brynjar
<x xml:space="preserve">Abstract</x> Objectives Vascular risk factor control may not only prevent stroke but also reduce the risk of dementia. We investigated whether a multifactorial intervention program reduces the incidence of cognitive symptoms one‐year after stroke and transient ischemic attack in first ever stroke patients without cognitive decline prior to the stroke. Materials and methods Patients suffering their first ever stroke were included in this randomized, evaluator‐blinded, controlled trial with two parallel groups. Baseline examination included extensive assessment of exposure to vascular risk factors and cognitive assessments regarding memory, attention, and executive function. After discharge, patients were allocated to either intensive vascular risk factor intervention or care as usual. The primary end points were changes in trailmaking test A and 10‐word test from baseline to 12 months follow‐up. Results One hundred ninety‐five patients were randomized. The difference between groups in trail‐making test A, adjusted for baseline measurements, was 3·8 s (95% confidence interval: −4·2 to 11·9; P = 0·35) in favor of the intervention group. The difference between groups in the 10‐word recall test was 1·1 words (95% confidence interval: −0·5 to 2·7; P = 0·17) in favor of the intervention group. We did not observe any differences in the secondary outcomes of incident dementia or mild cognitive impairment. Conclusions We could not demonstrate cognitive effects of an intensive risk factor intervention at one‐year poststroke. Longer follow‐up and a more heterogeneous study sample might have lead to larger effects. More effective methods for managing the risk of further cognitive decline after stroke are needed.